Single-nucleus RNA sequencing defines adipose tissue subpopulations that contribute to Tibetan pig cold adaptation - Jiali Liu; Yao Jiang; Tianxia Liu; Chuanhe Chen; Linya Chui; Along Cui; Xueping Zhang; Xiao Wang; Yu Wang; Chunhuai Yang; Ying Zhang; Tianwen Wu; et al. (BMC Biology)
Abstract Background Thermogenic beige adipocyte displays a remarkable ability in mammals to adapt to cold environments, but the underlying cellular mechanisms remain unclear, especially in pigs that lack functional UCP1. Results Multilocular beige adipocytes were observed in both Tibetan pigs (cold-tolerant) and Bama pigs (cold-sensitive) after short-term cold exposure (4 ℃ for 3 days). Through single-nucleus RNA sequencing of adipose tissues, including subcutaneous inguinal adipose tissues (IAT) and perirenal adipose tissues (PAT), from both pig breeds at room temperature and cold treatment conditions, we discovered two cell subpopulations specific to Tibetan pigs, PDGFRα + EBF2 High in IAT and ADIPOQ + HIF1A High in both depots. PDGFRα + EBF2 High cells were characterized as potential beige precursors, while ADIPOQ + HIF1A High cells were found to express highly thermogenic-related genes. Despite the decrease of the lipogenic subpopulation and the increase of the lipolytic and the thermogenic subpopulations observed in both pig breeds upon cold treatment, Tibetan pigs exhibited stronger cellular and molecular responses compared to Bama pigs. Remarkably, cold-induced de novo beige adipogenesis and white adipocyte browning, likely occurred in Tibetan pigs, while Bama pigs relied more heavily on white browning. Moreover, BMP7, which was highly expressed in the PDGFRα + EBF2 High subpopulation, positively regulates porcine beige thermogenic capacity. Conclusions Our data offers a comprehensive and unprecedented perspective on the heterogeneity and plasticity of adipose tissues of pigs and broadens the understanding of beige fat biology in mammals.